Fragmentation in a Bid to Defragment: Decentralisation as a Solution to the Challenge of Inclusion in the Kenyan Context - Mungai, Melissa (Strathmore Law Review, 2016)
Fragmentation is a practical tool suggested in this paper to bring about societal inclusion. Indeed, this is not a novel idea. Kenya has joined the league of practitioners of decentralisation, a system of governance that involves fragmentation. One of the objectives is to achieve national unity. The evil observed today is that decentralisation has brought about broadened separation. The aim of this paper is to highlight how decentralisation as a practical mechanism ought to unite. This is a possible solution to the challenge of inclusion. The end sought is a better society where unity, peace and justice abound. The paper will tackle three spheres of inclusion: social, political and economic which are dealt with separately but in essence they are interlinked with each other. In each of these areas, the paper will illustrate how fragmentation has achieved inclusion.